STRUCTURE AND COMPOSITION OF FLORAL AT MANGROVE FOREST IN PITAS SABAH MALAYSIA: Struktur dan Komposisi Bunga pada Hutan Mangrove di Pitas Sabah Malaysia - Andy R. Mojiol; Audrey Eliseus; Wahyudi Wahyudi (HUTAN TROPIKA, 2020)
The aim of the study was to determined and record mangrove species composition anddiversity at Pitas mangrove forest, Sabah. Mangroves forest occurs in waterlogged, saltysoils of sheltered tropical and subtropical shores. It usually found along the coastlinesthroughout the world, usually between 25º N longitude and 25º S latitude. This study wasconducted in Pitas district (N 06?43’, E 117?4’) which is located at the northern tip ofSabah, Malaysia. Whereas, Pitas district has an approximately 38,564 ha of the mangrovearea. In this study, the mangrove location covered an area ranges from Malawali island(N 07?2.023', E 117?16.883'), Tobo island (N 07?01.070', E 117?19.008'), Layak-layakisland (N 06?56.587', E 117?14.323'), Mapan-mapan (N 06?51.608', E 117?14.861'), andJambongan island (N 06?45.016', E 117?25.816'). The random sampling method wasdone with simple plots sizes of 20m x 20m to determine the species’ biodiversity,composition and structure. As a result, 13 mangrove species have been identified in allstudy locations namely known as Sonneratia caseolaris, Ceriops tagal, Bruguieragymnorhiza, Rhizophora mucronata, Aegiceras corniculatum, Avicennia marina,Rhizophora apiculata, Sonneratia alba, Bruguiera cylindrica, Lumnitzera littorea,Pemphis acidula, Scyphiphora hydrophyllacea, and Scaevola taccada. The result showsthat the Shannon –Wiener biodiversity index (H’) at the island and disturbed mangroveareas is less diverse (H’ below than 1.5) compared to the undisturbed mainland areaswith (H’=1.95). Sonneratia caseolaris is the dominant mangrove species in the islandwith the highest value of Important Value Index (IVI) with 144.77% compared to allspecies in the study location. These areas show the importance of ecological aspectswithin the forest ecosystem. Therefore, the protection and conservation of this mangrovein this area is a necessity.Keywords: Mangrove, species composition, diversity, Important Value Index (IVI),island, mainland, disturbed, Pitas Sabah